PROTOTIPE APLIKASI UJIAN CODING PHP BERBASIS WEB INTRANET DI STMIK ATMA LUHUR - Yohanes Setiawan Japriadi; Lukas Tommy (LPPM Nusa Mandiri, 2019)
Modernization causes the examination process in some educational institutions that are usually done conventionally now start to change to CBT (Computer Based Test). At STMIK Atma Luhur, CBT in the form of a coding test carried out on a computer laboratory was felt to be not effective enough due to a short correction time, as well as the possibility of lossing the students work due to sudden power failure. Collection of jobs using an LAN (Local Area Network) intranet network can not be realized due to the difficult network configuration and requires not a small cost. One solution that can be offered in overcoming the above problem is to create a web-based exam application that is connected to a Wireless Local Area Network (WLAN) intranet network. The system development model and tools used in this study are prototype models and UML (Unified Modeling Language). The proposed application is effective in facilitating and accelerating the process of collecting student answer files from several client computers to a server computer. In addition, the usage of the proposed application allows the lecturer not to correct students' answers in a hurry, so that the scores that are truly objective and can be accounted for are obtained.